Backbone Structure Effect on the Thermoelectric Properties of IDT‐Based p‐Type Conjugated Polymers. Issue 1 (18th September 2019) - Wu, Sicheng; Wu, Xiaoyu; Xing, Weilong; Sun, Yimeng; Zou, Ye; Xu, Wei; Zhu, Daoben
Abstract: Four conjugated polymers are synthesized through indacenodithiohene (IDT) unit copolymerized with thiophene and thiophene derivatives. Indacenodithiohene‐co‐thieno[3, 2‐b]thiophene (IDT‐TT) and indacenodithiohene‐co‐trans‐1, 2‐di(2‐thienyl)ethylene (IDT‐TVT) exhibit better charge transport mobilities than indacenodithiohene‐co‐thiophene (IDT‐T) and indacenodithiohene‐co‐3, 4‐ethoxylene dioxythiophene (IDT‐EDOT), and also display superior thermoelectric properties after doping. Theoretical calculations suggest that IDT‐EDOT and IDT‐TVT have better coplanarities; the inferior performance for IDT‐EDOT might be due to its low molecular weight. Meanwhile, it is worth mentioning that via the synergistic effect of two dopants (CN6CP, CuTFSI), the electrical conductivities of the polymers are further improved. The XPS data shows that the coordination interaction between copper ion and the cyano groups of CN6CP introduces cupric ions into the polymer films, which leads to the increase of the doping ratio. Abstract : Four IDT‐based polymers are synthesized, and the studies show that the polymers with extended conjugated building blocks exhibit advanced charge transport characteristics and better thermoelectric properties after doping. Furthermore, the addition of two dopants (CN6CP and CuTFSI) improves the electrical conductivities of the polymers, for the coordination interaction of the copper and the cyano groups in CN6CP.